2014
DOI: 10.5539/jas.v6n8p1
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Organic Wastes as Liming Materials in Low Input Rainfed Agricultural System

Abstract: A field experiment was conducted on an acid soil in a humid tropical Island of Andaman, India to explore the feasibility of using locally available organic wastes as liming materials after suitable composting. The organics such as coconut husk compost, poultry manure, vermicompost and gliricidia were incorporated at the rate of 20 Mg ha -1 and the amendment effect was compared with lime applied at the rate of 4 Mg ha -1. Soil application of composted organic wastes significantly increased the soil pH. The exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…It was found that though liming effect of RPs increased pH of acid soil to a few units, the reduction in available Al content in soil might have significant role in improving plant growth environment in highly acidic soils as observed in the present study. Similar results were observed by other workers where significant increase in soil pH and decrease in exchangeable Al content occurred in the soil incubated with different organic wastes like coconut husk compost, poultry manure and vermicompost (Wong et al, 1998;Swarnam and Velmurugan, 2014).…”
Section: Soil Incubation Experimentssupporting
confidence: 92%
“…It was found that though liming effect of RPs increased pH of acid soil to a few units, the reduction in available Al content in soil might have significant role in improving plant growth environment in highly acidic soils as observed in the present study. Similar results were observed by other workers where significant increase in soil pH and decrease in exchangeable Al content occurred in the soil incubated with different organic wastes like coconut husk compost, poultry manure and vermicompost (Wong et al, 1998;Swarnam and Velmurugan, 2014).…”
Section: Soil Incubation Experimentssupporting
confidence: 92%
“…Based on the analysis by comparing the diffraction pattern with the database, it clearly understood that the calcium extracted from H. opuntia had the same pattern as CaCO 3 . This result was connected with the statement of Swarnam et al (2021) that H. opuntia contains a high level of CaCO 3 within cells. The diffractogram pattern in this research was also the same as eggshells and seashells' which were exhibited by Supriyanto et al (2019) and Dampang et al (2019).…”
Section: Scanning Electron Microscope (Sem)supporting
confidence: 76%
“…These BLs may have liming potential through cations addition (K + , Ca 2+ , Mg 2+ , NH 4 + , etc.) (Mowrer et al., 2020; Swarnam & Velmurugan, 2014). We mixed the BL and soil and measured the pH (Table 3).…”
Section: Resultsmentioning
confidence: 99%